Predicting intracerebral hemorrhage growth with the spot sign: the effect of onset-to-scan time - Dowlatshahi, Dar; Brouwers, H. Bart; Demchuk, Andrew M.; Hill, Michael D.; Aviv, Richard I.; Ufholz, Lee-Anne; Reaume, Michael; Wintermark, Max; Hemphill, J. Claude; Murai, Yasuo; Wang, Yongjun; Zhao, Xingquan; et al. (Stroke, 2016)
Background and Purpose—Hematoma expansion after acute intracerebral hemorrhage is common and is associated with early deterioration and poor clinical outcome. The computed tomographic angiography (CTA) spot sign is a promising predictor of expansion; however, frequency and predictive values are variable across studies, possibly because of differences in onset-to-CTA time. We performed a patient-level meta-analysis to define the relationship between onset-to-CTA time and frequency and predictive ability of the spot sign.Methods—We completed a systematic review for studies of CTA spot sign and hematoma expansion. We subsequently pooled patient-level data on the frequency and predictive values for significant hematoma expansion according to 5 predefined categorized onset-to-CTA times. We calculated spot-sign frequency both as raw and frequency-adjusted rates.Results—Among 2051 studies identified, 12 met our inclusion criteria. Baseline hematoma volume, spot-sign status, and time-to-CTA were available for 1176 patients, and 1039 patients had follow-up computed tomographies for hematoma expansion analysis. The overall spot sign frequency was 26%, decreasing from 39% within 2 hours of onset to 13% beyond 8 hours (P<0.001). There was a significant decrease in hematoma expansion in spot-positive patients as onset-to-CTA time increased (P=0.004), with positive predictive values decreasing from 53% to 33%.Conclusions—The frequency of the CTA spot sign is inversely related to intracerebral hemorrhage onset-to-CTA time. Furthermore, the positive predictive value of the spot sign for significant hematoma expansion decreases as time-to-CTA increases. Our results offer more precise risk stratification for patients with acute intracerebral hemorrhage and will help refine clinical prediction rules for intracerebral hemorrhage expansion.
Gesehen am 27.04.2020